GAMBARAN TINGKAT PENGETAHUAN REMAJA PUTRI TENTANG KEPUTIHAN DI SEKOLAH TINGGI ILMU KESEHATAN YOGYAKARTA - MELINA, FITRIA (Jurnal Kesehatan Samodra Ilmu (JKSI), 2021)
ABSTRACT Background: Based on data from the World Health Organization (WHO), poor women's reproductive health problems have reached 33% of the total burden of disease suffered by women in the world, one of which is vaginal discharge (Oriza, 2018). According to (WHO), women rarely pay attention to the cleanliness of their external genitalia. Vaginal infections every year affect women worldwide 10-15% of 100 million women, for example, adolescents who are infected with candida bacteria around 15% and experience vaginal discharge Research methods: This research method is descriptive. This research was conducted in July 2021. The sample in this study were students of STIkes Yogyakarta, totaling 32 respondents and using purposive sampling. The instrument in this study was a knowledge questionnaire Results and discussion: The level of knowledge of young women about vaginal discharge in the sufficient category 15 respondents (46.9%), the level of knowledge about the meaning of vaginal discharge in the good category 15 respondents (46.9%), the level of knowledge of young women about the type of vaginal discharge in the sufficient category 17 respondents (53 ,1%), the level of knowledge of young women about the causes of vaginal discharge in the sufficient category 13 respondents 40.6%), the level of knowledge of young women about the signs and symptoms of vaginal discharge in the category of 16 respondents (50.0%), the level of knowledge of young women about prevention of vaginal discharge in the category enough 14 respondents (43.8), the level of knowledge of young women about the treatment of vaginal discharge in the sufficient category 15 people (46.9%) and the level of knowledge of young women about the treatment of vaginal discharge in the category less 25 respondents (78.1%).